Thermal properties of cool asphalt concrete containing phase change material - Mizwar, I.K. (Institute of Physics Publishing, 2019)
Building and pavement, due to their impervious nature, are listed as some of the main causes for Urban Heat Island (UHI) phenomena where the temperature in the urban area is higher than that of surrounding areas. Due to its characteristic that can absorb and release heat at a specific temperature, Phase Change Materials (PCM) has been widely used in building infrastructure as thermal regulation to combat UHI. However, the application of PCM in pavement infrastructure is still very limited due to a lack of study on this. This study analyses the Phase Change Material in asphalt concrete focussing on thermal properties, which is surface temperature. Experiments were carried out on a slab of wearing course with the PCM substituting the equivalent amount of mineral filler, and then compared with a slab of conventional wearing course. The study showed that the potential of PCM used in pavement mixture decreased the surface temperature of the pavement. The maximum difference of temperature of PCM and asphalt concrete mixture reached 120C. Â© 2019 IOP Publishing Ltd. All rights reserved.